Influência da compatibilização interfacial seletiva nas propriedades mecânicas de compósitos híbridos ternários de PET/fibra de vidro/elastômeros olefínicos reativos - Carvalho, Gustavo Baldi de (Universidade Federal de São Carlos, 2009)
Poly(ethylene terephthalate) (PET) is a semi-crystalline thermoplastic widely used for packaging of aereted soft drinks, which makes the recycling of post-consumer PET material necessary to prevent the negative environmental impact of its disposal. The recycling of PET as an engineering thermoplastic can be accomplished by the incorporation of glass fiber (GF) and elastomeric impact modifier to the PET matrix, forming a ternary hybrid composite. To assure an appropriate balance of mechanical properties of stiffness, strength and toughness in this composite, it is important that the GF and rubber particles are dispersed separately in the matrix, avoiding the encapsulation of the fibers by the rubber phase and promoting, simultaneously GF reinforcement and rubber toughening mechanisms. In this work, the influence of selective interfacial compatibilization on the mechanical properties of hybrid composites of recycled PET was studied, as the matrix polymer was modified with reactive olefin elastomers of E-MA-GMA and E-EA-MAH, as well as with short GF treated with either epoxy (FV952) or aminesilanes (FV983). Ternary systems of PET/E-MA-GMA/FV952, PET/E-MA-GMA/FV983 and PET/E-EA-MAH/FV983 were compounded in a twin-screw corotating ZSK-30 extruder and, depending on the relative reactivities of PET s chain-end groups with the functionalities present on the GF surfaces and in the E-MA-GMA and E-EA-MAH terpolymers, the GF is encapsulated or not by the elastomer phase and, consequently, the mechanical properties of the hybrid composites are affected differently. Mechanical tests and torque rheometry data indicated high reactivity between PET and E-MA-GMA terpolymer, and low reactivity with the E-EA-MAH. Analysis of tensile and Izod impact tests results, as well as from fiber-polymer interfaces observations by SEM, indicated good fiber-polymer adhesion in PET/E-MA-GMA/FV952 and PET/E-MA-GMA/FV983 systems, and fiber encapsulation by rubber particles in the case of the PET/E-EA-MAH/FV983 system.
Influence of selective interfacial compatibilization on the mechanical properties of ternary hybrid composites of Pet/Glass Fiber/Reactive olefin elastomers
Keywords: Polímeros; PET - reciclado; Elastômeros olefínicos; Compósitos poliméricos; Compatibilização interfacial; Propriedades mecânicas; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::POLIMEROS